Comparative review of the nutritional value of cold-pressed pumpkin (Cucurbita pepo L.) seed oil of different origins - Rabrenovic Biljana B.; Vujasinovic Vesna B.; Novakovic Miroslav M.; Corbo Selma; Basic Zorica N. (Hemijska Industrija, 2016)
The objective of this study was to investigate the nutritional value of seven samples of cold pressed a pumpkin oil of different origins and influence of seed origin on the content of the most important bioactive components. Four samples of a pumpkin oil is obtained by cold pressing of the seeds of domestic and Austrian varieties, and three samples of cold pressed oils were obtained from the seeds of unknown origin, taken by free choice in the market. As indicators of the nutritional values are determined by the composition and content of fatty acids, tocopherols and sterols. In the composition of the fatty acid were oleic dominant (34,2±0,09 - 43,9±0,04%) and linolenic fatty acid (30,8±0,09 - 46,9±0,015%). This study confirmed that the oil pumpkin dominant ?+?-tocopherol, whose contents ranged from 34,65±0,03 to 44,59±0,69 mg/100g. We determine the composition and content of ?7 phytosterols, especially for specific oil pumpkins. Was detected five ?7 sterol: Spinasterol, ?7,22,25-stigmastatrienol, ?7,25-stigmastadienol, ?7-stigmasterol and ?7-avenasterol. Dominant its content was ?7,22-stigmastadienol or Spinasterol with 39,98 to 50,31% of the total content of sterols.